Effective modernisation of public administration: The experience of India - Select cases - Surayya, Teki (2008)
The article studies modernisation of India public administration, through select cases. A public administrator should have marketing attitude to evolve right services for people. This requires administrator going to people for consultations in making policies. Implementation of VAT is an example of modernisation of tax administration. Jammabhoomi and Joint Forest Management programmes in which public administration played modern facilitator role is a successful case of Citizen Participation in modern public administration. Fiscal component of decentralisation transfers authority to local governments empowering them to finance (INR 6075 million) fund through issues to bonds from public, to provide infrastructure for people and Kerala Forest Revolving Fund for teak and pulp wood are cases of effective modernisation of Administration and decentralisation. Citizen participation, decentralisation including fiscal management, strategic management approaches, etc. are fundamental pillars for effective modernisation of public administration. - Reproduced.
Keywords: Public administration - India; Public administration